2017
DOI: 10.1002/tie.21911
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Social Networking for Talent Management: An Exploratory Study of Indian Firms

Abstract: Utilizing the social capital and social network theories, this research explores and highlights how social networking has been strategically utilized as an effective tool by organizations for employer branding and innovative talent acquisition strategies in India. Qualitative data from 78 semistructured interviews with human resources ( HR ) professionals of information technology ( IT ), information technology-enabled services ( ITeS ), and talent acquisition organizations confi rm the growing utilization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 65 publications
0
22
0
1
Order By: Relevance
“…This adaptability resource can be manifested among Indian IT employees through their greater accountability towards the career that perhaps make them engage in networking and competencies development activities. The present organizational culture of Indian IT companies encourages professionals to build networks, promotes innovation, and provides scopes for skill advancement (Kumar, 2015; Nayak, Bhatnagar, & Budhwar, 2018). Consequently, Indian IT individuals, being accountable for own career growth, may perceive staying in the same organization as an advantageous deal (Raman, Bharathi, Allen, & Joseph, 2013).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…This adaptability resource can be manifested among Indian IT employees through their greater accountability towards the career that perhaps make them engage in networking and competencies development activities. The present organizational culture of Indian IT companies encourages professionals to build networks, promotes innovation, and provides scopes for skill advancement (Kumar, 2015; Nayak, Bhatnagar, & Budhwar, 2018). Consequently, Indian IT individuals, being accountable for own career growth, may perceive staying in the same organization as an advantageous deal (Raman, Bharathi, Allen, & Joseph, 2013).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…14,25 Hence employee management is becoming a strong challenge for the HR professionals working in India as correctly pointed by many respondents in this study. 69 While the interview results suggest that social media are extensively getting leveraged in different processes of the organizations, most of the HR managers and HR professionals reported that nowadays organizations are exploiting social media extensively for managing their employees in several ways: such as recruitment and selection, employer branding, employee engagement, employee engagement and supporting existing literature on such kind of studies. Besides, almost all participants accepted the risks involved in the high usage of social media concerning employee as well as organization privacy.…”
Section: Discussionmentioning
confidence: 72%
“…Researches conducted in the HRM domain mainly utilise SNSs' definitions of Boyed & Ellison (2007) (Black & Johnson, 2012;Brown & Vaughn, 2011;Kluemper et al, 2016;Nayak et al, 2018;Rienties et al, 2010;Suen, 2018) or Kaplan &Haenlein (2010) (Aguado et al, 2016;Arjomandy, 2016;Kluemper et al, 2016;Martin et al, 2015;Poba-Nzaou et al, 2016;Vetráková et al, 2018). Boyed & Ellison (2007) define social network sites as "web-based services that allow individuals to (1) construct a public or semi-public profile within a bounded system, (2) articulate a list of other users with whom they share a connection, and (3) view and traverse their list of connections and those made by others within the system.…”
Section: Definition Of Social Networkmentioning
confidence: 99%